"Habilidad investigativa para la elaboración de Tesis de Bachiller de Enfermería - UNT" - Llanos Rodríguez, Daniela Lina (2017)
The present research of quantitative type, descriptive method, was realized in the Faculty of Nursing of the National University of Trujillo - 2017; With the purpose of determining the Level of Investigative Ability for the Elaboration of Thesis of Bachelor of Nursing. The sample universe consisted of 34 theses published in the year 2016. For the collection of data the instrument was used: Rubric for the evaluation of the thesis report, taken from the Regulation of Degrees and Titles RD No. 511 of the Faculty of Nursing of The National University of Trujillo (2008) and modified by the authors. The results were presented in simple one-dimensional tables, one entry, with numerical and percentage frequencies. The results obtained show a high level of investigative ability, in the following aspects: Title, 100 percent; Introduction, 94.1 percent; Methodology, 97.1 percent; Results, 100 percent; Analysis and Discussion, 52.9 percent; Conclusions, 91.1 percent; While in the Bibliography there is a low level of investigative ability with 88.3 percent. Concluding that of the total number of theses reviewed, 58.8 percent have a high level of investigative ability and 41.2 percent have an average level of investigative ability.